Bacillus Calmette–Guérin in Immuno-Regulation of Alzheimer’s Disease - Klein, Benjamin Y.; Greenblatt, Charles L.; Gofrit, Ofer N.; Bercovier, Hervé (Frontiers in Aging Neuroscience, 2022)
Although this focused review stresses the “proof of concept” that BCG can reduce the risk of AD, intravesical BCG cannot be entertained as a method of immunotherapy or immunoprophylaxis in normal adults. It does however, argue that the living BCG organism acts systemically, and its administration by other routes proves this. In Brazil oral BCG continued in use until the late 1980’s and even as a further test it was used successfully to treat superficial bladder cancer. Further proof of the systemic action of BCG, has been provided by Hoft et al. whose studies of PO and ID BCG have shown that both give a systemic Th1 and IFN-? response, although PO administration yielded a better IgA and bronchoalveolar Tcell reaction and ID application a better Th1 one. Strains of BCG show variation in their effectiveness, but research aimed at understanding these differences and engineering the bacterium to even greater effectiveness is underway. Lastly, routine vaccinations for elderly adults, whether or not the beneficial effect on dementia is overstated, should be considered on a patient’s check list by every geriatrician.